2006
DOI: 10.1063/1.2388941
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of postprocessing of dense nanotube arrays by neutral and ion fluxes

Abstract: The advantages of using low-temperature plasma environments for postprocessing of dense nanotube arrays are shown by means of multiscale hybrid numerical simulations. By controlling plasma-extracted ion fluxes and varying the plasma and sheath parameters, one can selectively coat, dope, or functionalize different areas on nanotube surfaces. Conditions of uniform deposition of ion fluxes over the entire nanotube surfaces are obtained for different array densities. The plasma route enables a uniform processing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…It should be noted that the previous simulation studies [11][12][13][14][15][16] on the plasma growth of nanostructures have shown that the ion coverage is affected by varying the process parameters. Therefore, although this non-uniformity is not significant, the experimental conditions should be adjusted to maximize the uniformity of passivation of the textured Si surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the previous simulation studies [11][12][13][14][15][16] on the plasma growth of nanostructures have shown that the ion coverage is affected by varying the process parameters. Therefore, although this non-uniformity is not significant, the experimental conditions should be adjusted to maximize the uniformity of passivation of the textured Si surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] The model is applicable for the investigation of the effect of the plasma environment on the growth of the nanostructured surfaces. This model has recently been advanced to include the effect of the cone-like nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Using the macroscopic formulation from Refs. [2,39,40], we can write the dimensionless energy of an adatom as [2] …”
Section: Discussion and Analysismentioning
confidence: 99%
“…[3][4][5][6][7][8] In most of these applications, high aspect ratio and vertically aligned nanostructures 9 can sustain a high electron current and strong electron field emission from the sharp tips, which often have a radius of curvature of several nanometers. [10][11][12] Such applications impose very strict requirements on the height uniformity of the carbon nanostructures throughout the entire array. Indeed, a nonuniform array that consists of nanostructures of different lengths cannot provide adequate emission parameters ͑e.g., current density and service lifetime͒ due to overload.…”
Section: Introductionmentioning
confidence: 99%